Kidneys and adrenal glands of Caiman yacare (Daudin, 1802) (Crocodylia: Alligatoridae): morphology and morphometry - MARIANA O. LIMA; LEONARDO L. GORZA; EDUARDO JOSÉ S. BORGES; YHURI C. NÓBREGA; LEONARDO O. TRIVILIN; RODRIGO G. FIGUEIREDO; MARIA APARECIDA DA SILVA (Anais da Academia Brasileira de Ciências)
Abstract Crocodilians are semi-aquatic reptiles with highly sophisticated anatomy and physiology that are well adapted to dwell in freshwater environments or be exposed to brackish and saltwater, indicating the complex nature of the organization and function of the urinary system in these animals. The objective of this work is to describe the morphology of the kidneys and adrenal glands of Caiman yacare, providing morphometric comparisons between male and female animals. It is concluded that macroscopically, the kidneys had an elongated oval shape, reddish-brown color, and greater width in the middle region. The kidneys are associated with the wall of the coelomic cavity, together with the adrenal glands and gonads. Histologically, the renal structure consisted, from the outer periphery to the inner core, of the collecting tubules, the cortical region, the proximal and distal convoluted tubules, the renal corpuscles and the medullary region. The adrenal glands are composed of two types of tissue: adrenocortical tissue and chromaffin tissue. Morphometric analyzes revealed that male kidneys exceeds female kidneys in most macroscopic biometric dimensions. The diameter of the renal corpuscles for both sexes was greater in the caudal portion of the right kidney, and in the middle portion of the left kidney, for males.